Virulence genes of avian pathogenic Escherichia coli isolated from commercial chicken in Nepal. (April 2023) - Bhattarai, Rebanta Kumar; Basnet, Hom Bahadur; Dhakal, Ishwari Prasad; Alocilja, Evangelyn C.
Abstract: Colibacillosis is the most common bacteriological disease in poultry. The purpose of this study was to determine the recovery rate of avian pathogenic Escherichia coli (APEC) strains, the distribution, prevalence of Escherichia coli Reference (ECOR) collection and virulence associated gene (VAG) in four types of chickens infected by colibacillosis. Commercial broilers and layers had the highest percentage of positive APEC isolates (91%). We confirmed the ECOR phylogroup including B1 and E for the first time in Nepal. The prevalences of these phylogroups among chicken types were significantly different (p < 0.001). Among 57 VAGs, the number of genes found per isolate ranged from 8 to 26, with the top 5 VAGs being fimH (100%), iss a (92.2%), traT a (90.6%), sit chro . (86%), and ironEC (84.8%). We found significant differences in gene prevalence among the chicken types. The predominance of B1 and E, and the VAG patterns suggest considering ECOR phylogroup and VAGs while formulating strategies for the prevention and control of APEC. Highlights: We reported avian pathogenic Escherichia coli Reference (ECOR) phylogroups for the first time in Nepal. APEC phylogroup B1 and E were predominant in broiler, broiler breeder, layer, and layer breeder chickens. The APEC strains isolates contained 8–26 virulence-associated genes, with fimH the most frequently detected. The relationships between phylogroup and overall VAG patterns were significantly correlated at a 1% level of significance.